Questions that are at the core of a mathematics education project - Bicudo, Maria Aparecida Viggiani [UNESP] (Springer Nature, 2023)
The claims and discussion presented in this chapter are articulated by the question How to account for the different views offered in the many lines of research within the realm of mathematics education, so as to avoid being held hostage by it, while seek nuclear ideas that articulate such diversity. This chapter argues that the intertwining between pre-categorial and categorial knowledge underlies the diversity of views, the respective perspectives in which they are created and, above all, the imposition of the mathematical-scientific-technological way of conceiving and treating worldly reality. Crucial themes for this conception, such as exactness and mathematization, are highlighted. Another argument is that the contemporary world view established and practiced by science and technology has become absolute and led to the loss of meaning within human life. It also contends that it is crucial for mathematics education to work with such types of knowledge, through an exercise of philosophical, thus critical, and reflective thinking, aiming to emphasize the importance and meaning of the science and technology present in the contemporary world, as well as highlight that they do not dictate and are not of the guardians of truth, much less establish the parameters that should guide human knowledge and the ethics of personal and social interrelations.
Keywords: Categorial knowledge; Exactness; Mathematics education; Mathematization; Pre-categorial knowledge